Sex Education in Islamic Education Perspective - Pristian Hadi Putra; Yelni Erniyati (Institut Agama Islam Negeri (IAIN) Curup, 2022)
This study aims to describe sex education in Islamic perspective, because by knowing sex education, and if it is understood correctly especially by the teenagers, they will be protected from sexual deviations.. The researcher used qualitative research with a library research approach. Data collection techniques are carried out by searching and collecting data from various sources such as books, literature, documents, journals, and from the print media regarding sex education in the perspective of Islamic education. Obtained data are then synthesized which eventually becomes a conclusion. The data found revealed sex education in Islamic perspective is an integral part of the education of faith, morals and worship. It is related to how to behave in society in order to prevent the sex abuse. Moreover, sex education problems in Indonesia are still tends to be shallow, and the delivery of sex education is still ineffective, including delivery only at school and the delivery is focused only on explaining reproductive organs. The delivery of sex education must be planned. It starts from the time baby is born, from the curious traits that guide the development of his thinking, and brain intelligence, so that the family as informal education is carried out properly.